Peer support as a buffer: reducing math anxiety through psychological resilience in left-behind rural students - Chao Wang; Xin-yue Li; Xin-yi Lin (Humanities & Social Sciences Communications)
Abstract Math anxiety is a prevalent issue among junior high school students, particularly those in rural areas with left-behind experiences who often receive insufficient attention in research and interventions. Rural left-behind children face higher academic stress and mental health risks due to long-term parental absence, and peer support and psychological resilience may serve as important protective factors in alleviating their math anxiety. This study involved 572 junior high school students from rural settings who completed the Peer Support Scale, Math Anxiety Scale, and Youth Psychological Resilience Scale. The findings indicate that peer support is negatively associated with math anxiety, with psychological resilience mediating this relationship. Additionally, the left-behind experience significantly moderates the relationship between psychological resilience and math anxiety. The findings suggest that peer support indirectly reduces math anxiety by enhancing psychological resilience, but that the experience of staying behind weakens this protective effect. This study highlights the importance of fostering supportive peer interactions and enhancing resilience to address educational challenges faced by vulnerable rural students, especially those with a left-behind experience. It also emphasizes the need to design more targeted interventions to support these students.